Community Genetics: Avaluation of a course based on video lessons - Pustilnick, Renato; Poerner, Fabiana; Furtado Alle, Lupe (Guará Journal, 2017)
Genetic alterations are amongst the most prominent causes of death in the Brazilian population. Considering there is a lack of information on the subject. The objective of the present study was to create and evaluate the effectiveness of a video lessons based course in community genetics for the early identification of suggestive signs of genetic disease. The course was offered online with 1228 subscribers, 428 graduates and 800 dropouts. A pre and a post-test were applied. Although the evasion was greater than the reported from the Distance Education Brazilian Association report (2014; p<0,05), the average scores were significantly high-er in the post-test (p < 0.05). The model positively impacted the learning level of participants, presenting itself as an alternative to be applied on a large scale in Brazil, including in other areas of knowledge